Financing the Operation and Maintenance Costs of Hurricane Protection Infrastructure Options for the State of Louisiana - Miller, Trey (RAND Corporation, 2012)
This report analyzes the fiscal capacity of eight local levee districts in southern Louisiana to shoulder the burden of operating and maintaining the Hurricane and Storm Damage Risk Reduction System and other key hurricane protection infrastructure currently under construction by the U.S. Army Corps of Engineers, specifically focusing on operation and maintenance costs.